2012
DOI: 10.1163/156854012x633385
|View full text |Cite
|
Sign up to set email alerts
|

Brachyuran crabs (Decapoda, Brachyura) associated with the green sponge Amphimedon viridis (Demospongiae) from Itaguá Beach, south-eastern coast of Brazil

Abstract: This study provides information on the community structure of brachyuran crabs associated with the green sponge, Amphimedon viridis Duchassaing & Michelotti, 1864, from a beach on the southeastern coast of Brazil. Monthly collections from May 2002 through August 2003 were carried out on the rocky bottoms off Itaguá Beach (23°27 07 S 45°02 49 W). Crabs on the green sponge banks were hand-caught during snorkelling sessions, and 638 crabs belonging to 31 species, 19 genera, and 10 families were obtained. Biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
7
0
4
Order By: Relevance
“…Decapods may also use other living organisms as food and shelter. Sponge crab species carry upon their carapace sponge pieces or other organic materials to camouflage themselves from predators and to obtain their food by cutting some sponge fragments [ 39 ]. The emerald crabs seek refuge and protection among the tentacles of sea anemones [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Decapods may also use other living organisms as food and shelter. Sponge crab species carry upon their carapace sponge pieces or other organic materials to camouflage themselves from predators and to obtain their food by cutting some sponge fragments [ 39 ]. The emerald crabs seek refuge and protection among the tentacles of sea anemones [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The difference in sizes recorded in this study, when compared with those reported by Negreiros-Fransozo and Fransozo (2003), seem to corroborate the results of Conde and Díaz (1992), which demonstrated that crabs in estuarine and riverine environments reach larger sizes when compared to crabs in hypersaline and marine habitats. Alves et al (2012a;2012b) also recorded a similar mean size for specimens of P. austrobesus from the Vitoria Archipelago (mean size = 5.4 ± 1.5 mm CW) and Itaguá Beach (mean size = 6.9 ± 4.6 mm CW), both of which are on the northeastern coast of São Paulo state, Brazil. It is probable that the negative association between the absolute abundance of P. austrobesus in the conditions of salinity and bottomwater temperature recorded in this investigation can be explained by the same reasons.…”
Section: Discussionmentioning
confidence: 58%
“…Second, the restricted size can also be an adaptation for exploiting the microhabitats in the farming nets. Alves et al (2012a;2012b) may corroborate this hypothesis, as the nets obtained crabs from rock crevices, which also offer small-sized refuges. Third, estuarine areas had a larger productivity than marine areas.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations